Lignin graded porous carbon material with large-size micropores as well as preparation method and application of lignin graded porous carbon material
Through the combined activation of sulfomethylated lignin, potassium carboxylate and metal carbonate, a lignin-grade porous carbon material with large-sized micropores was prepared, which solved the low proportion of micropores and few mesoporous pores in the prior art. The problem is that high specific surface area and excellent zinc ion capacitance performance are achieved, and are suitable for zinc ion hybrid capacitors.
Patent Information
- Application Number
- CN202411639379.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing lignin porous carbon materials have problems in zinc ion hybrid capacitors with low micropore ratio, few mesoporous pores, and poor zinc storage specific capacitance and rate performance. Traditional processes are difficult to disperse lignin and activators evenly, and the assembly driving force is weak. Inefficient and requires a large amount of strong corrosion agent or high temperature for a long time treatment.
Using sulfomethylated organic solvents insoluble lignin, water-soluble potassium carboxylate and water-insoluble metal carbonate as carbon sources and template agents, lignin graded porous carbon with large-sized micropores are prepared by rapid antisolvent precipitation and high-temperature carbonization. Materials, using weak etching of potassium carboxylate and pyrolysis of metal carbonate to form large-sized micropores and mesopories.
It significantly improves the specific surface area and mesoporosis of lignin-grade porous carbon materials, and has a high proportion of micropores in large sizes. It shows excellent capacitance performance as a positive electrode material of zinc ion hybrid capacitors, avoids the use of strong corrosive agents and shortens the preparation time. It is suitable for Industrialized production.
Smart Images

Figure CN119191287A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of porous carbon materials, and in particular relates to a lignin graded porous carbon material with large-sized micropores, and a preparation method and application thereof. Background Art
[0002] Zinc ion hybrid capacitors are composed of a battery-type zinc negative electrode and a capacitor-type carbon positive electrode. They integrate the advantages of zinc ion batteries and supercapacitors and have good application prospects in electric vehicles, portable and flexible devices. However, commercial activated carbon as a carbon positive electrode has the problems of low specific capacitance and poor rate performance. It is difficult to match the battery-type zinc negative electrode in terms of energy storage dynamics, which limits the application of zinc ion hybrid capacitors. Therefore, it is urgent to prepare high-specific capacitance carbon positive electrode materials for the construction of high-performance zinc ion hybrid capacitors. The hierarchical porous structure helps to enhance the energy storage dynamics of the porous carbon positive electrode. The size of hexahydrated zinc ions is about 0.86nm. By constructing micropores with a size greater than 0.86nm and larger mesopores, storage sites and diffusion paths can be provided for hydrated zinc ions, thereby improving the zinc storage specific capacitance and rate performance of the porous carbon positive electrode.
[0003] Lignin has a wide range of sources, high carbon content, rich conjugated benzene ring structure and active oxygen-containing functional groups, and is an ideal carbon material precursor. Porous carbon materials with high specific surface area can be prepared by chemical activation. Zhang et al. (J. Colloid. Interf. Sci. 2023, 635, 94-104) used K 2 CO 3 and CaCl 2 Activated lignin was prepared with a specific surface area of 984 m 2 / g, with an average pore size of 3.9nm; Xue et al. (Chem. Eng. J. 2024, 480, 147994) used urea and potassium oxalate to activate lignin and prepared a porous carbon nanosheet with a specific surface area of 2276m 2 / g of microporous carbon material. The above method directly mixes lignin and a large amount of activated additives, and the materials are difficult to disperse evenly, resulting in a large number of micropores smaller than hydrated zinc ions in the carbon material structure, and a lack of large-sized mesopores, which is not conducive to the diffusion and transmission of zinc ions.
[0004] In order to improve the ion transmission power, the researchers used weakly corrosive metal salts as templates and prepared hierarchical porous carbon materials rich in mesopores by solution coprecipitation or assembly. Chinese patent CN201911111152.8 hydrothermally reacts lignin and basic carbonate to obtain a lignin / basic carbonate mixture, and then performs high-temperature carbonization to prepare a high-mesoporous porous carbon material. The material contains fewer micropores larger than the size of hydrated zinc ions, and the specific surface area is only 485m 2 / g, cannot be used as a zinc storage positive electrode; Chinese patent CN202111233499.7 co-precipitates lignin with soluble calcium salts and soluble carbonates to prepare lignin / nano-CaCO 3 Composite, and high specific surface area lignin graded porous carbon was prepared by high temperature carbonization. This material has excellent performance as an adsorbent, but there are few mesopores larger than 4nm in the structure, which is not suitable as a high-rate zinc storage carbon positive electrode; Chinese patent CN202410852533.6 mixed organic zinc salt, potassium hydroxide and lignin in an alcohol solution to prepare lignin / nano zinc oxide / organic potassium salt composite, and prepared high mesoporous lignin-based porous carbon material by carbonization. Due to the poor complexing ability of lignin and organic zinc salt, a large amount of zinc salt is required in the preparation process, which increases the preparation cost; Chinese patent CN201811375772.8 prepared a composite by adding ethanol to a mixed dispersion of lignin sulfonate and metal oxalate, and prepared a porous carbon nanosheet rich in mesopores by high temperature carbonization. However, the weaker force causes the process to be assembled six times, and the preparation efficiency is low; Fu et al. (Chem. Eng. J. 2020, 392, 12372) used sodium lignin sulfonate solution to complex zinc ions and oxalate ions, and prepared sodium lignin sulfonate / zinc oxalate complexes by slowly adding ethanol, and prepared lignin carbon nanosheets by high-temperature carbonization. This process requires strict control of the ethanol drip rate, the process is time-consuming, and the precipitation rate of the lignin complex is low; Chen et al. (Angew. Chem. Int. Ed. 2024, 63, e202316116) used an antisolvent precipitation method to add an aqueous solution of ammonium citrate and sodium chloride to ethanol to obtain a composite salt assembly, and prepared a porous carbon material with rich large mesopores by carbonization, but the small molecule carbon source-ammonium citrate is easily decomposed by heat, and the carbon yield is only 8%, which is not conducive to large-scale preparation.
[0005] In summary, the lignin porous carbon material as the positive electrode of zinc ion hybrid capacitor has the following problems:
[0006] (1) In terms of the preparation process of lignin precursors, it is difficult to evenly disperse lignin, activators and templates by direct mixing, while the conventional solution assembly method has a weak driving force for lignin assembly, is time-consuming, and has poor efficiency, resulting in a low precipitation rate of the lignin composite precursor.
[0007] (2) In terms of the structural regulation of lignin porous carbon materials, the traditional activation method can prepare porous carbon materials with high specific surface area, but excessive activator introduces a large number of micropores whose sizes do not match the hydrated zinc ions, and the mesopores are scarce. Using a single weakly corrosive metal salt such as basic carbonate, calcium carbonate or zinc oxalate as a template can prepare carbon materials rich in mesopores, but the micropores are few and the pore size is difficult to control.
[0008] (3) In terms of zinc storage performance, the proportion of micropores larger than 0.86 nm in lignin porous carbon materials is low and the mesopore volume is small, resulting in low zinc storage specific capacitance and poor rate performance. Summary of the invention
[0009] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a lignin graded porous carbon material with large-sized micropores.
[0010] The method of the present invention uses sulfomethylated organic solvent-insoluble lignin as a carbon source, a water-soluble potassium carboxylate as an activator, and a water-insoluble metal carbonate as a template agent, and prepares a lignin hierarchical porous carbon material with large-sized micropores through rapid anti-solvent precipitation and high-temperature carbonization. First, lignin is dissolved in a water / organic solvent mixed solvent, and the filter residue is separated to obtain the organic solvent-insoluble lignin. The organic solvent-insoluble lignin is dissolved in a sodium hydroxide solution, sulfite and aldehydes are added, and the sulfomethylated organic solvent-insoluble lignin solution is obtained by dialyzing after heating reaction. The sulfomethylated organic solvent-insoluble lignin, the water-soluble potassium carboxylate and the water-insoluble metal carbonate are made into a dispersion and uniformly mixed, poured into a high-speed stirred organic solvent, and the solid-liquid separation and drying are performed after standing to obtain a lignin / potassium salt / metal carbonate complex, which is carbonized at high temperature and acid-etched to obtain a lignin hierarchical porous carbon material with large-sized micropores.
[0011] In the preparation process of the method of the present invention, lignin is dissolved in a water / organic solvent mixed solvent to obtain organic solvent-insoluble lignin, which is then subjected to sulfomethylation modification, thereby effectively increasing the solubility difference of lignin in water and organic solvent, enhancing the assembly force between lignin and potassium carboxylate and metal carbonate in the anti-solvent precipitation process, significantly shortening the assembly time and improving the precipitation efficiency; in the carbonization process of the lignin / potassium carboxylate / metal carbonate composite, weak etching of the potassium carboxylate and gas released by pyrolysis of the metal carbonate can generate relatively large micropores, and metal oxides formed by pyrolysis of the metal carbonate can support the lignin carbon skeleton to generate mesopores with relatively large pore sizes, thereby forming a hierarchical porous carbon material with large micropores, which is used as the positive electrode of a zinc ion hybrid capacitor, can provide storage sites and diffusion channels for hydrated zinc ions, and exhibits excellent capacitance performance.
[0012] Another object of the present invention is to provide a lignin graded porous carbon material having large-sized micropores prepared by the above method.
[0013] Another object of the present invention is to provide an application of the above-mentioned lignin graded porous carbon material with large-sized micropores in zinc ion battery positive electrode materials and / or zinc ion hybrid capacitor positive electrode materials.
[0014] In the present invention, the specific surface area of the lignin graded porous carbon material with large-sized micropores is not less than 1200 m2 / g, the proportion of micropores larger than 0.86nm is not less than 50% of the total micropores, and the mesoporosity is not less than 60%.
[0015] The purpose of the present invention is achieved through the following solutions:
[0016] A method for preparing a lignin graded porous carbon material with large-sized micropores, characterized in that it comprises the following steps:
[0017] (1) dissolving lignin in a mixed solvent of water / organic solvent, filtering out the residue and drying it to obtain organic solvent-insoluble lignin;
[0018] (2) dissolving the organic solvent-insoluble lignin obtained in step (1) in a sodium hydroxide solution, controlling the solution pH to 10-12, adding sulfite and aldehydes, reacting at 80-100° C. for 2-4 hours, dialyzing and concentrating the reaction solution to obtain a lignin concentrate;
[0019] (3) mixing the lignin concentrate obtained in step (2) with a potassium carboxylate solution and a metal carbonate dispersion, and after sufficient stirring, pouring the mixture into a high-speed stirring organic solvent, stirring for 5 to 20 minutes, letting it stand, filtering, and drying the precipitate to obtain a lignin / potassium carboxylate / metal carbonate complex;
[0020] (4) placing the lignin / potassium carboxylate / metal carbonate complex obtained in step (3) in an inert atmosphere for carbonization, soaking the carbonized product in dilute acid, filtering, and drying to obtain a lignin hierarchical porous carbon material having large-sized micropores;
[0021] The mass ratio of the solute content in the lignin, sulfite, aldehyde, potassium carboxylate solution and the metal carbonate content in the metal carbonate dispersion is 100:(30-120):(40-160):(100-300):(100-300).
[0022] Preferably, the mass ratio of the solute content in the lignin, sulfite, aldehyde, potassium carboxylate solution, and the metal carbonate content in the metal carbonate dispersion is 100: (60-80): (60-100): (150-200): (150-200);
[0023] The concentration of the potassium carboxylate solution and the metal carbonate dispersion is 20-200 g / L.
[0024] Preferably, in step (1), the organic solvent is one or more of acetone, ethanol, ethylene glycol, etc.; and the volume ratio of water to the organic solvent is 3:(5-10).
[0025] Preferably, in step (2), the sulfite is one or more of sodium sulfite, sodium bisulfite, etc.;
[0026] The aldehydes are one or more of formaldehyde, glyoxal, glutaraldehyde, etc.;
[0027] The dialysis refers to dialyzing the reaction solution in deionized water for 20 to 30 hours using a dialysis bag with a molecular weight cutoff of 1000Da;
[0028] The concentration refers to heating and concentrating the lignin concentrate at 80-100° C. until the mass concentration of the lignin concentrate is 30-50%.
[0029] Preferably, in step (3), the potassium carboxylate is one or more of potassium oxalate, potassium citrate, potassium acetate, and potassium tartrate;
[0030] The metal carbonate is one or more of basic zinc carbonate, basic magnesium carbonate, basic lead carbonate, and calcium carbonate;
[0031] The volume ratio of the mixed liquid to the organic solvent is 1:(2-6);
[0032] The organic solvent is one or more of ethanol, acetone and ethylene glycol.
[0033] Preferably, in step (4), the carbonization temperature program is: heating to 200-350°C at 5-15°C / min, maintaining for 1-2h; then heating to 600-900°C at 1-10°C / min, maintaining for 2-4h and then cooling;
[0034] The inert atmosphere is at least one of nitrogen and argon;
[0035] The dilute acid refers to one or more of nitric acid, sulfuric acid and hydrochloric acid with a concentration of 0.5 to 2 mol / L, and the soaking time is 12 to 24 hours.
[0036] Preferably, the lignin is at least one of bagasse alkali lignin, corn cob alkali lignin, bamboo alkali lignin, wheat straw alkali lignin and enzymatic lignin in a biorefining process.
[0037] Preferably, in step (1), the volume ratio of water to organic solvent is 3:7;
[0038] In step (2), the pH is adjusted to 11.5;
[0039] In step (3), the volume ratio of the mixed solution to the organic solvent is 1:3.5-4;
[0040] In step (4), the carbonization temperature program is: heating to 250°C at 10°C / min, maintaining for 1 hour; then heating to 700°C at 5°C / min, maintaining for 2.5 hours; the concentration of the dilute acid is 1 mol / L;
[0041] The drying method in steps (1), (3) and (4) is at least one of infrared drying, forced air drying, vacuum drying and freeze drying, the drying temperature is 50 to 200° C., and the drying time is 2 to 48 hours.
[0042] The method of the present invention prepares a lignin graded porous carbon material with large-sized micropores.
[0043] The invention discloses an application of the lignin graded porous carbon material with large-sized micropores in positive electrode materials of zinc ion batteries and / or positive electrode materials of zinc ion hybrid capacitors.
[0044] In step (1) of the present invention, a mixed solvent of acetone, ethanol, ethylene glycol, etc. and water is used to dissolve lignin in order to separate and obtain organic solvent-insoluble lignin. In the step, the volume ratio of water to organic solvent needs to be controlled to be 3: (5-10), preferably 3: 7. Too high or too low a water volume fraction is not conducive to the dissolution of lignin, which will cause the lignin in step (3) to dissolve in the solvent and reduce the assembly force.
[0045] In order to obtain sulfomethylated lignin with good water solubility and abundant ion binding sites, the mass ratio of lignin to sulfite and aldehydes needs to be controlled to be 100:30-120:40-160, preferably 100:(60-80):(60-100). If the weight ratio of lignin is too low, the grafting efficiency will be poor; if the weight ratio of lignin is too high, the degree of sulfomethylation will be low and the water solubility of lignin will be poor.
[0046] The reaction temperature of this step is 80-100°C and the reaction time is 2-4 hours. If the reaction temperature is too low or the reaction time is too short, it is not conducive to sulfomethylation grafting; if the reaction temperature is too high or the reaction time is too long, lignin will be degraded and the reaction yield will be reduced.
[0047] The dialysis step is to remove residual sodium hydroxide, sulfite, aldehydes, and improve the purity of lignin concentrate. The molecular weight cutoff of the dialysis bag used is 1000Da. If the molecular weight cutoff is too low, impurities will not be completely removed; if the molecular weight cutoff is too high, the yield of lignin concentrate will be reduced.
[0048] The purpose of heating and concentrating the lignin solution in this step is to increase the concentration of the lignin solution. The mass fraction of the concentrated solution needs to be controlled at 30-50%. If the mass fraction of the concentrated solution is too low, the precipitation efficiency of step (3) will be reduced; if the mass fraction of the concentrated solution is too high, the lignin / potassium carboxylate / metal carbonate complex obtained in step (3) will be uneven.
[0049] Step (3) is to utilize the significant difference in solubility of sulfomethylated organic solvent-insoluble lignin in water and organic solvent, and to quickly prepare a lignin / potassium carboxylate / metal carbonate complex based on anti-solvent precipitation.
[0050] This step requires controlling the concentration of the potassium carboxylate solution and the metal carbonate dispersion. If the concentration is too low, the lignin precipitation is incomplete; if the concentration is too high, the lignin, potassium carboxylate and metal carbonate are not evenly compounded. This step requires fully stirring the mixed solution so that the lignin, potassium carboxylate and metal carbonate form a uniform dispersion system.
[0051] In this step, the mixed solution is poured into the organic solvent under high-speed stirring. The stirring speed needs to be strictly controlled. If the stirring speed is too low, the materials will be unevenly dispersed. The stirring time is 5 to 20 minutes. If the stirring time is too short, the lignin, potassium carboxylate and metal carbonate cannot be completely precipitated; if the stirring time is too long, the preparation efficiency will be affected.
[0052] In this step, the volume ratio of the mixed liquid to the organic solvent needs to be controlled at 1:2-6, preferably 1:3.5-4. If the volume ratio of the organic solvent is too low, the solubility of lignin is large, the assembly force with potassium carboxylate and metal carbonate is weak, and the precipitation rate of the complex is low; if the volume ratio of the organic solvent is too high, the preparation cost is increased.
[0053] The inert atmosphere of step (4) can be other inert gases such as nitrogen or argon. Carbonization is divided into two stages. The temperature of the first stage is required to be 200-350°C and the time is 1-2h. If the carbonization temperature is too low or the time is too short, it will be unfavorable for the metal carbonate to release gas to activate lignin. The second stage is required to be in the range of 600-900°C and the time is 2-4h. If the temperature or time is too short, it will lead to incomplete carbonization of lignin and incomplete activation of potassium carboxylate, and the specific surface area of the product is low; if the temperature is too high or the time is too long, it will not only increase the production cost, but also cause the potassium carboxylate to be over-activated, resulting in the destruction of the pore structure and low product yield.
[0054] The concentration of the dilute acid solution in this step is required to be in the range of 0.5 to 2 mol / L, and the immersion time is controlled at 12 to 24 hours. If the acid concentration is too low or the immersion time is too short, metal impurities will remain and the conductivity of the product will be reduced; if the acid concentration is too high or the immersion time is too long, the microporous structure of the product will be destroyed.
[0055] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0056] (1) Compared with the lignin porous carbon material prepared by traditional chemical activation, the lignin graded porous carbon material with large-sized micropores prepared by the present invention has larger micropore diameter and mesoporosity, and the proportion of micropores larger than 0.86 nm is high, which can provide storage sites and diffusion paths for hydrated zinc ions, so that it has higher capacitance performance as a positive electrode material for zinc ion hybrid capacitors.
[0057] (2) The present invention uses potassium carboxylate as an activator and metal carbonate as a template, and uses an anti-solvent co-precipitation method to enhance the assembly force, so as to efficiently prepare a lignin composite precursor in one step, thereby avoiding the use of strong corrosive reagents and shortening the preparation time, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a scanning electron microscope image of the lignin graded porous carbon with large-sized micropores obtained in Example 1 of the present invention.
[0059] Figure 2 It is the nitrogen adsorption / desorption isotherm and pore size distribution curve of the lignin graded porous carbon with large-sized micropores obtained in Example 1 of the present invention.
[0060] Figure 3 These are the charge and discharge curves of the electrode prepared from the lignin graded porous carbon with large-sized micropores obtained in Example 1 of the present invention at different current densities.
[0061] Figure 4 It is the specific capacitance of the lignin graded porous carbon with large-sized micropores obtained in Example 1 of the present invention at different current densities.
[0062] Figure 5 It is the charge and discharge curve of the electrode prepared by the lignin porous carbon obtained in Comparative Example 3 of the present invention at different current densities.
[0063] Figure 6 It is the specific capacitance of the lignin porous carbon obtained in Comparative Example 3 of the present invention at different current densities. DETAILED DESCRIPTION
[0064] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0065] The materials involved in the following examples can all be obtained from commercial channels.
[0066] Example 1
[0067] Weigh 100g of purified corn cob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0068] Weigh 150g of potassium oxalate and dissolve it in 1000ml of water, weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / potassium oxalate / basic zinc carbonate composite solid powder;
[0069] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 2.5h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0070] Example 2
[0071] Weigh 100g of purified alkali lignin from bamboo and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water and place the filter residue in an infrared drying oven at 70℃ and dry for 6h to obtain organic solvent-insoluble lignin; dissolve the organic solvent-insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, then add 60g sodium bisulfite and 60g glyoxal, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ and evaporate to obtain 200ml of lignin concentrate with a mass concentration of 30%;
[0072] Weigh 150g potassium citrate and dissolve it in 1000ml water, weigh 200g basic zinc carbonate and disperse it in 1000ml water, mix the two with the above 200ml lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / potassium citrate / basic zinc carbonate complex solid powder;
[0073] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 800℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0074] Example 3
[0075] Weigh 100g of purified wheat straw alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, then add 60g sodium bisulfite and 60g glutaraldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 150ml of lignin concentrate with a mass concentration of 40%;
[0076] Weigh 200g of potassium acetate and dissolve it in 1000ml of water, weigh 200g of basic magnesium carbonate and disperse it in 1000ml of water, mix the two with the above 150ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100°C forced air drying oven for 12h to obtain a lignin / potassium acetate / basic magnesium carbonate composite solid powder;
[0077] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0078] Example 4
[0079] Weigh 100g of purified bagasse alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0080] Weigh 150g of potassium tartrate and dissolve it in 1000ml of water, weigh 150g of basic lead carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of acetone solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100°C forced air drying oven for 12h to obtain a lignin / potassium tartrate / basic lead carbonate composite solid powder;
[0081] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 4h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0082] Example 5
[0083] Weigh 100g of purified enzymatic lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 200ml of lignin concentrate with a mass concentration of 30%;
[0084] Weigh 150g of potassium oxalate and dissolve it in 1000ml of water, weigh 200g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 200ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethylene glycol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100°C forced air drying oven for 12h to obtain a lignin / potassium oxalate / basic zinc carbonate complex solid powder;
[0085] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 600℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0086] Example 6
[0087] Weigh 100g of purified corn cob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, then add 60g sodium bisulfite and 60g glyoxal, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0088] Weigh 200g of potassium citrate and dissolve it in 1000ml of water, weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100°C forced air drying oven for 12h to obtain a lignin / potassium citrate / basic zinc carbonate complex solid powder;
[0089] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 900℃ at 5℃ / min and maintained for 2h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0090] Comparative Example 1 (Compared with Example 1, water-ethanol mixed solvent was not used to extract lignin)
[0091] Weigh 100g purified corn cob alkali lignin and dissolve it in 1000ml sodium hydroxide solution, adjust the pH to 11.5, then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature and dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, the dialyzate is heated and evaporated at 85℃ to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0092] Weigh 150g of potassium oxalate and dissolve it in 1000ml of water, weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / potassium oxalate / basic zinc carbonate composite solid powder;
[0093] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0094] Comparative Example 2 (Compared with Example 1, sulfomethylation reaction was not carried out using sodium bisulfite and formaldehyde)
[0095] Weigh 100g of purified corncob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and dialyze the solution in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate and obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0096] Weigh 150g of potassium oxalate and dissolve it in 1000ml of water, weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / potassium oxalate / basic zinc carbonate composite solid powder;
[0097] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0098] Comparative Example 3 (Compared with Example 1, no anti-solvent co-precipitation was used, and the mixed solution of lignin concentrate, potassium oxalate and basic zinc carbonate was directly evaporated)
[0099] Weigh 100g of purified corn cob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0100] Weigh 150g of potassium oxalate and dissolve it in 1000ml of water, weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then evaporate the water at 85℃ to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / potassium oxalate / basic zinc carbonate composite solid powder;
[0101] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0102] Comparative Example 4 (Compared with Example 1, potassium hydroxide was used to replace potassium oxalate)
[0103] Weigh 100g of purified corn cob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0104] Weigh 150g of potassium hydroxide and dissolve it in 1000ml of water, weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix the two with the above 120ml of lignin concentrate and stir them thoroughly for 2h, then pour them into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100°C forced air drying oven for 12h to obtain a lignin / potassium hydroxide / basic zinc carbonate composite solid powder;
[0105] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0106] Comparative Example 5 (Compared with Example 1, only potassium oxalate was used as an activator)
[0107] Weigh 100g of purified corn cob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0108] Weigh 150g of potassium oxalate and dissolve it in 1000ml of water, mix it with the above 120ml of lignin concentrate and stir it for 2h, then pour it into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / potassium oxalate complex solid powder;
[0109] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0110] Comparative Example 6 (Compared with Example 1, only basic zinc carbonate was used as a template)
[0111] Weigh 100g of purified corn cob alkali lignin and add it to a mixed solution of 600ml water and 1400ml ethanol. After ultrasonic stirring, filter with water, and place the filter residue in a 70℃ infrared drying oven for 6h to obtain organic solvent insoluble lignin; dissolve the organic solvent insoluble lignin in 1000ml sodium hydroxide solution, adjust the pH to 11.5, and then add 60g sodium bisulfite and 60g formaldehyde, and react at 85℃ for 3h under stirring. After the reaction is completed, the reaction solution is cooled to room temperature, and then dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of 1000Da. After dialysis for 24h, heat the dialyzate at 85℃ to evaporate to obtain 120ml of lignin concentrate with a mass concentration of 50%;
[0112] Weigh 150g of basic zinc carbonate and disperse it in 1000ml of water, mix it with the above 120ml of lignin concentrate and stir it thoroughly for 2h, then pour it into 8000ml of ethanol solvent with high-speed stirring, keep stirring for 10min, let it stand and separate to obtain a precipitate, and dry the precipitate in a 100℃ forced air drying oven for 12h to obtain a lignin / basic zinc carbonate composite solid powder;
[0113] Take 10g of the above powder and place it in a tubular furnace for high-temperature carbonization under the protection of a nitrogen atmosphere. The carbonization temperature is increased from room temperature to 250℃ at 10℃ / min and maintained for 1h; then the temperature is increased to 700℃ at 5℃ / min and maintained for 3h. After carbonization, it is cooled to room temperature to obtain a black powder. The black powder is soaked in 500ml of 1mol / L hydrochloric acid solution, stirred for 12h, filtered and washed with deionized water, and placed in a vacuum oven at 100℃ for 24h to obtain a lignin graded porous carbon material with large-sized micropores.
[0114] Example Effect Description
[0115] The structure of the lignin graded carbon materials obtained in the examples and comparative examples was characterized and their performance in the positive electrode material of zinc ion hybrid capacitor was tested. The results are shown in Tables 1 to 2 and Figure 1 to Figure 6 .
[0116] The microstructure of the samples was characterized by scanning electron microscopy (SEM, Hitachi SU8220). The specific surface area and pore structure of the samples were tested using a fully automatic specific surface and porosity analyzer (Micromeritics ASAP 2020 instrument).
[0117] In the performance test of zinc ion hybrid capacitor, the lignin carbon material obtained by the present invention, acetylene black and polytetrafluoroethylene were prepared in a mass ratio of 8:1:1 to prepare the working electrode, the zinc sheet was used as the negative electrode, and 1M ZnSO 4 The electrolyte was assembled into a button capacitor for electrochemical testing. The test window was 0.2-1.8V, and the charge and discharge current density was 0.1-50A / g.
[0118] Table 1 shows the pore structure parameters of lignin hierarchical porous carbon materials prepared in different embodiments and comparative examples.
[0119] Table 2 shows the specific capacitance of lignin graded porous carbon materials prepared in different embodiments and comparative examples.
[0120] Table 1 Pore structure characteristic parameters of lignin graded porous carbon materials
[0121]
[0122]
[0123] Table 2 Specific capacitance of lignin graded porous carbon materials
[0124]
[0125] Description of Table 1 and Table 2:
[0126] The specific surface areas of the lignin graded porous carbon materials prepared in Examples 1 to 6 all exceeded 1200 m 2 / g, the proportion of large-sized micropores is greater than 50%, and the proportion of mesopores is greater than 60%. The specific surface area of Example 1 is as high as 1633m 2 / g, and the total pore volume is 1.68cm 3 / g, the large-size microporosity is 64.6%, and the mesoporosity is as high as 65.4%. Its specific surface area is much higher than that of the lignin porous carbon material obtained by extracting lignin without using a water-ethanol mixed solvent in Comparative Example 1, the lignin porous carbon material obtained by sulfomethylation without using sodium bisulfite and formaldehyde in Comparative Example 2, the lignin porous carbon material obtained by directly evaporating the precursor in Comparative Example 3, the lignin porous carbon material obtained by activation with potassium oxalate alone in Comparative Example 5, and Comparative Example 6. The large-size microporosity and mesoporosity are much higher than that of the lignin porous carbon material obtained by activation with potassium hydroxide in Comparative Example 4.
[0127] The performance test results of the zinc ion hybrid capacitor in Table 2 show that the lignin graded porous carbon obtained in Example 1 has excellent specific capacitance and capacitance retention. At a current density of 0.1A / g, the specific capacitance is 445F / g, and at a current density of 50A / g, the specific capacitance remains at 180F / g, which is much higher than that of Comparative Examples 1 to 6, indicating that the lignin graded porous carbon prepared by the technology of the present invention is superior to the lignin porous carbon prepared by the traditional method.
[0128] Compared with Example 1, Comparative Example 1 does not use a water-ethanol mixed solvent to extract lignin, resulting in a high solubility of lignin in the ethanol solvent during the assembly process, low precipitation efficiency of lignin with potassium oxalate and basic zinc carbonate, uneven composite, weakened activation effect, and a specific surface area of the obtained lignin porous carbon (850m 2 / g) and total pore volume (0.88 cm 3 / g) are significantly lower than those in Example 1, resulting in extremely poor specific capacitance and rate performance.
[0129] Compared with Example 1, Comparative Example 2 does not perform sulfomethylation reaction on lignin, resulting in weak assembly driving force, lignin cannot be evenly compounded with potassium oxalate and basic zinc carbonate, carbonization activation effect is poor, and the specific surface area of the obtained lignin porous carbon (922m 2 / g) and total pore volume (1.01 cm 3 / g) are significantly lower than those in Example 1, resulting in extremely poor specific capacitance and rate performance.
[0130] Compared with Example 1, Comparative Example 3 did not use anti-solvent co-precipitation, but directly evaporated the mixed solution of lignin concentrate and potassium oxalate and basic zinc carbonate, resulting in uneven mixing of lignin / potassium oxalate / basic zinc carbonate complex, weakening the activation effect of potassium oxalate and basic zinc carbonate, and the specific surface area of the obtained lignin porous carbon (1039m 2 / g), total pore volume (1.23cm 3 / g) and mesoporosity (48.8%) are lower than those in Example 1, resulting in poor specific capacitance and capacitance retention.
[0131] Compared with Example 1, Comparative Example 4 uses potassium hydroxide instead of potassium oxalate. Potassium hydroxide is highly corrosive and easily introduces a large number of micropores that do not match the size of hydrated zinc ions. The obtained porous carbon material has a high specific surface area (1728 m 2 / g), but the large-size microporosity (32.5%) and mesoporosity (50.4%) are lower than those in Example 1, resulting in poor specific capacitance and capacitance retention.
[0132] Compared with Example 1, Comparative Example 5 only uses potassium oxalate as an activator. The activation efficiency of a single potassium salt is poor, and the lignin aggregation structure cannot be fully opened. The specific surface area of the obtained lignin porous carbon (918 m2 / g), total pore volume (0.50cm 3 / g), large-size microporosity (36.7%) and mesoporosity (10.2%) are significantly lower than those of the sample obtained in Example 1, resulting in extremely poor specific capacitance and capacitance retention.
[0133] Compared with Example 1, Comparative Example 6 only used basic zinc carbonate as the template, the activation effect was poor, the number of micropores in the obtained lignin porous carbon was insufficient, and the specific surface area (749m 2 / g) and large-size micropore volume (0.12 cm 3 / g) are lower than those of the sample obtained in Example 1, resulting in extremely poor specific capacitance and capacitance retention.
[0134] In summary, the anti-solvent precipitation method and the combined activation of potassium carboxylate and metal carbonate of the present invention can prepare lignin graded porous carbon materials with high specific surface area and abundant large-sized micropores, which, as positive electrode materials for zinc ion hybrid capacitors, show significantly better performance than lignin porous carbon materials prepared by traditional methods.
[0135] Figure 1 This is a scanning electron microscope image of the lignin graded porous carbon material prepared in Example 1 of the present invention. It can be seen that it presents an interconnected flaky porous carbon structure with an open skeleton and abundant pores.
[0136] Figure 2 It is the nitrogen adsorption-desorption curve and pore size distribution curve of the lignin graded porous carbon material obtained in Example 1 of the present invention. The adsorption amount of its nitrogen adsorption-desorption curve increases significantly in the low-pressure zone, indicating the presence of micropores. Obvious hysteresis loops appear in the medium-pressure zone and the high-pressure zone, indicating the presence of mesopores, so the material has graded porous properties. The pore size distribution curve shows that its micropore distribution is concentrated in 0.7-1.0nm and 1-2nm, the mesopore distribution is concentrated in 4-50nm, and the macropore is concentrated in 70nm. Its micropores and mesopores are attributed to the activation of the gas released by the pyrolysis of potassium oxalate and basic zinc carbonate and the etching of potassium compounds, while the macropores are related to the zinc oxide generated in situ.
[0137] Figure 3 The following are the charge and discharge curves of the lignin graded porous carbon material prepared in Example 1 of the present invention as the positive electrode material of the zinc ion hybrid capacitor at different current densities. All curves are quasi-triangular, and there is no obvious voltage drop at high current density, indicating that the material has ideal capacitance characteristics.
[0138] Figure 4The lignin graded porous carbon material prepared in Example 1 of the present invention has a specific capacitance of 445F / g (0.1A / g), 369F / g (0.2A / g), 303F / g (0.5A / g), 270F / g (1.0A / g), 250F / g (2.0A / g), 227F / g (5.0A / g), 214F / g (10A / g), 200F / g (20A / g) and 180F / g (50A / g), showing excellent performance and good application potential.
[0139] Figure 5 and Figure 6 The charge and discharge curves and specific capacitance of the lignin porous carbon obtained in Comparative Example 3 of the present invention as the positive electrode material of the zinc ion hybrid capacitor at different current densities are as follows, and the specific capacitance is 319F / g (0.1A / g), 277F / g (0.2A / g), 231F / g (0.5A / g), 212F / g (1.0A / g), 198F / g (2.0A / g), 184F / g (5.0A / g), 163F / g (10A / g), 118F / g (20A / g) and 78F / g (50A / g), which shows a performance that is significantly inferior to that of Example 1, indicating that the anti-solvent co-precipitation technology for preparing the lignin composite precursor proposed in the present invention is significantly better than the conventional evaporation technology.
Claims
1. A method for preparing a lignin graded porous carbon material with large-sized micropores, characterized in that: The following steps are involved: (1) dissolving lignin in a mixed solvent of water / organic solvent, filtering out the residue and drying it to obtain organic solvent-insoluble lignin; (2) dissolving the organic solvent-insoluble lignin obtained in step (1) in a sodium hydroxide solution, controlling the solution pH to 10-12, adding sulfite and aldehydes, reacting at 80-100° C. for 2-4 hours, dialyzing and concentrating the reaction solution to obtain a lignin concentrate; (3) mixing the lignin concentrate obtained in step (2) with a potassium carboxylate solution and a metal carbonate dispersion, and after sufficient stirring, pouring the mixture into a high-speed stirring organic solvent, stirring for 5 to 20 minutes, letting it stand, filtering, and drying the precipitate to obtain a lignin / potassium carboxylate / metal carbonate complex; (4) placing the lignin / potassium carboxylate / metal carbonate complex obtained in step (3) in an inert atmosphere for carbonization, soaking the carbonized product in dilute acid, filtering, and drying to obtain a lignin hierarchical porous carbon material having large-sized micropores; The mass ratio of the solute content in the lignin, sulfite, aldehyde, potassium carboxylate solution and the metal carbonate content in the metal carbonate dispersion is 100:(30-120):(40-160):(100-300):(100-300).
2. The method for preparing a lignin graded porous carbon material with large-sized micropores according to claim 1, characterized in that: The mass ratio of the solute content in the lignin, sulfite, aldehyde, potassium carboxylate solution, and the metal carbonate content in the metal carbonate dispersion is 100: (60-80): (60-100): (150-200): (150-200); The concentration of the potassium carboxylate solution and the metal carbonate dispersion is 20-200 g / L.
3. The method for preparing a lignin graded porous carbon material with large-sized micropores according to claim 2, characterized in that: In step (1), the organic solvent is one or more of acetone, ethanol, ethylene glycol, etc.; the volume ratio of water to the organic solvent is 3:(5-10).
4. The method for preparing a lignin graded porous carbon material with large-sized micropores according to claim 3, characterized in that: In step (2), the sulfite is one or more of sodium sulfite, sodium bisulfite, etc.; The aldehydes are one or more of formaldehyde, glyoxal, glutaraldehyde, etc.; The dialysis refers to dialyzing the reaction solution in deionized water for 20 to 30 hours using a dialysis bag with a molecular weight cutoff of 1000Da; The concentration refers to heating and concentrating the lignin concentrate at 80-100° C. until the mass concentration of the lignin concentrate is 30-50%.
5. The method for preparing a lignin graded porous carbon material with large-sized micropores according to claim 4, characterized in that: In step (3), the potassium carboxylate is one or more of potassium oxalate, potassium citrate, potassium acetate, and potassium tartrate; The metal carbonate is one or more of basic zinc carbonate, basic magnesium carbonate, basic lead carbonate, and calcium carbonate; The volume ratio of the mixed liquid to the organic solvent is 1:(2-6); The organic solvent is one or more of ethanol, acetone and ethylene glycol.
6. The method for preparing a lignin graded porous carbon material with large-sized micropores according to claim 5, characterized in that: In step (4), the carbonization temperature program is: heating to 200-350°C at 5-15°C / min, maintaining for 1-2h; then heating to 600-900°C at 1-10°C / min, maintaining for 2-4h and then cooling; The inert atmosphere is at least one of nitrogen and argon; The dilute acid refers to one or more of nitric acid, sulfuric acid and hydrochloric acid with a concentration of 0.5 to 2 mol / L, and the soaking time is 12 to 24 hours.
7. The method for preparing a lignin graded porous carbon material with large-sized micropores according to any one of claims 1 to 6, characterized in that: The lignin is at least one of bagasse alkali lignin, corn cob alkali lignin, bamboo alkali lignin, wheat straw alkali lignin and enzymatic lignin in a biorefining process.
8. The method for preparing a lignin graded porous carbon material with large-sized micropores according to claim 7, characterized in that: In step (1), the volume ratio of water to organic solvent is 3:7; In step (2), the pH is adjusted to 11.5; In step (3), the volume ratio of the mixed solution to the organic solvent is 1:3.5-4; In step (4), the carbonization temperature program is: heating to 250°C at 10°C / min, maintaining for 1 hour; then heating to 700°C at 5°C / min, maintaining for 2.5 hours; the concentration of the dilute acid is 1 mol / L; The drying method in steps (1), (3) and (4) is at least one of infrared drying, forced air drying, vacuum drying and freeze drying, the drying temperature is 50 to 200° C., and the drying time is 2 to 48 hours.
9. The lignin graded porous carbon material with large-sized micropores prepared by the method according to any one of claims 1 to 8.
10. Use of the lignin graded porous carbon material with large-sized micropores according to claim 9 in positive electrode materials for zinc ion batteries and / or positive electrode materials for zinc ion hybrid capacitors.
Citation Information
Patent Citations
Lignin porous carbon nanosheet as well as preparation method thereof and application in supercapacitor electrode material
CN109485029A
A high-mesoporous lignin hierarchical porous carbon material, its preparation method and application
CN112794324B
Lignin-based hierarchical porous carbon material with high mesoporous rate as well as preparation method and application of lignin-based hierarchical porous carbon material
CN118702102A
Structure-controllable multi-dimensional porous carbon material and preparation method thereof
CN111620338A
High-mesoporous-rate lignin hierarchical pore carbon material and preparation method and application thereof
CN112794324A
